Pengaruh Efikasi Diri (Self Efficacy) Terhadap Kemandirian Belajar Siswa - Ewy Diryatika; Armiati Armiati (Universitas Negeri Padang, 2023)
This study aims to determine the effect of self-efficacy on independent learning. The sample of this research is 217 students. Collecting data using a questionnaire. This type of research is quantitative research. The method of data analysis is in the form of descriptive analysis, simple regression analysis, hypothesis testing. It can be concluded if there is a significant influence between self-efficacy on student learning independence. Self-efficacy has a positive impact on independent learning. While 57% influenced by other variables.